Understanding health worker data use in a South African antiretroviral therapy register. Issue 11 (19th September 2018) - Jobson, Geoffrey; Murphy, Joshua; van Huyssteen, Mea; Myburgh, Hanlie; Hurter, Theunis; Grobbelaar, Cornelis J.; Struthers, Helen E.; McIntyre, James A.; Peters, Remco P. H.
Abstract: Objective: To evaluate how electronic data management systems affect data use practices in antiretroviral therapy (ART) programs within local health districts, and individual health facilities. Methods: We used a data quality audit to establish a baseline of the quality of data in the electronic register alongside in‐depth interviews with health workers and managers, to understand perceptions of data quality, data use by facility staff and challenges affecting data use. Results: The findings provide a four‐level continuum of data use that can be applied to other settings and recommendations for optimising facility‐level data use. Conclusion: By defining four levels of data use our findings suggest the potential to encourage a structured process of moving from passive data use, to more active and engaged data use, where data could be used to anticipate patient behaviour and link that behaviour to differentiated care plans.